A companion to Korean American studies - Joo, Rachael Miyung, 1975-; Lee, Shelley Sang-Hee, 1975- (Brill's companions to the Americas: history, societies, environments and cultures, 2018)
A Companion to Korean American Studies presents interdisciplinary works from a number of authors who have contributed to the field of Korean American Studies. This collection ranges from chapters detailing the histories of Korean migration to the United States to contemporary flows of popular culture between South Korea and the United States. The authors present on Korean American history, gender relations, cultural formations, social relations, and politics. Contributors are: Sohyun An, Chinbo Chong, Angie Y. Chung, Rhoanne Esteban, Sue-Je Lee Gage, Hahrie Han, Jane Hong, Michael Hurt, Rachael Miyung Joo, Jane Junn, Miliann Kang, Ann H. Kim, Anthony Yooshin Kim, Eleana Kim, Jinwon Kim, Ju Yon Kim, Kevin Y. Kim, Nadia Y. Kim, Soo Mee Kim, Robert Ji-Song Ku, EunSook Lee, Se Hwa Lee, S. Heijin Lee, Shelley Sang-Hee Lee, John Lie, Pei-te Lien, Kimberly McKee, Pyong Gap Min, Arissa H. Oh, Edward J.W. Park, Jerry Z. Park, Josephine Nock-Hee Park, Margaret Rhee and Kenneth Vaughan.